Pelatihan Dan Pendampingan Peningkatan Kinerja Usaha Berbasis Strategi Dan IT Pada Pelaku UMKM Hasil Olahan Laut Di Desa Labuan Pandeglang, Banten - Rianto , Muhammad Richo; Woestho, Choiroel (Jurnal Pengabdian kepada Masyarakat UBJ, 2022)
The purpose of this community service is to provide education, training and assistance in improving strategy and IT-based business performance for seafood MSME in the village of Labuan Banten. This training focuses on solving product problems that do not have Branding, packaging, are not hygienic, do not have traditional sales and marketing strategies and low average sales. Solutions for the problem is training and assistance in Branding and packaging strategies as well as the use of digital marketing are alternative solutions to problems in the short term to improve the performance of seafood MSME in Labuan village. It is hoped that after this activity is carried out, the MSME can have strong Branding, good packaging and a wide range of buyers and in the end can directly increase sales and indirectly help the regional economy and families.